Rock- and palaeomagnetic investigations of an Upper Pleistocene loess–palaeosol sequence near Süttő, Hungary - Christian Rolf; Ulrich Hambach; Ágnes Novothny; Erzsébet Horváth; Elisabeth Schnepp (PANGAEA, 2020)
A thorough rock- and palaeomagnetic investigation of an almost 13-m-thick Upper Pleistocene loess–palaeosol sequence (LPSS) outcropping near the village of Süttő in northern Hungary was conducted to obtain rock magnetic and palaeomagnetic-based chronostratigraphies. The results of our rock magnetic investigations indicate that the classical “Chinese” model of magnetic enhancement, showing increasing concentration-dependent rock magnetic parameters in the course of pedogenesis, is also valid for the northern Carpathian Basin. We constructed a relative geomagnetic palaeointensity (RPI) record for the central part of the section by using the natural remanent magnetisation (NRM) after demagnetisation in alternating fields of 15 mT and by employing anhysteretic remanent magnetisation (ARM), low-field susceptibility (Klf) and “saturation” remanent magnetisation (“S”IRM) as normalisers. The three obtained RPI data sets show almost identical trends and are therefore regarded as reliable recorders of the palaeointensity of the Earth extquotesingles magnetic field. The obtained RPI record allows for indirect dating of the LPSS at Süttő by correlation with the GLOPIS and the PISO stack. The derived age model is in agreement with the OSL-based chronostratigraphy, but contradicts the chronology based on the correlation between the susceptibility record and marine isotope stratigraphy (MIS), which gives rise to the hypothesis of a possible decoupling of the palaeoclimate in the Carpathian Basin and the marine realm during early MIS 3.